Penerapan Pencatatan Akuntansi Berdasarkan SAK EMKM (Studi Kasus UMKM Kripik Kulit Ikan Patin) - Islamiati, Nanda Elfrida; Nuraini, Fitri; Soedjono, Soedjono (JCA (Jurnal Cendekia Akuntansi), 2023)
Micro, small and medium enterprises (MSMEs) are one of the economic sector businesses that have an important role in advancing the economy in Indonesia. As a business operating in the MSME economic sector, of course it cannot be separated from the activities of preparing financial reports. However, in practice there are still many MSME players who have not prepared financial reports in accordance with Financial Accounting Standards. The purpose of this research is to find out how to prepare financial reports for the "Nyonya Patin" Leather Chips UMKM and carry out accounting records based on SAK EMKM. This type of research is qualitative descriptive research. The qualitative research method used is a case study approach. The results of this research indicate that the owner of the "Nyonya Patin" Leather Chips UMKM still does not carry out accounting records based on SAK EMKM and only records cash receipts and disbursements. By implementing SAK EMKM for the "Nyonya Patin" Leather Chips MSME, the financial reports are prepared using an accrual basic.